The AAA handbook 2011 : a new dimension - Barclays Capital; Barclays Bank (London Barclays Bank, 2011)
The handbook offers expanded coverage to take account of the growth in the European supernationals, agencies, sub-sovereign and covered bonds market.
oif 16/07/2018
Ref.
Keywords: Debts; Bonds; Europe